A one-pot multistep cyclization yielding thiadiazoloimidazole derivatives - Samanta, Debabrata; Rana, Anup; Bats, Jan W.; Schmittel, Michael (Beilstein Journal of Organic Chemistry, 2014)
A versatile synthetic procedure is described to prepare the benzimidazole-fused 1,2,4-thiadiazoles 2a–c via a methanesulfonyl chloride initiated multistep cyclization involving the intramolecular reaction of an in-situ generated carbodiimide with a thiourea unit. The structure of the intricate heterocycle 2a was confirmed by single-crystal X-ray analysis and its mechanism of formation supported by DFT computations.
Keywords: carbodiimide; cyclization; dithiourea; DFT; 1,2,4-thiadiazoles